Uitdraai Amsterdamse pamflettenkatalogus, 1960-1999 (in bewerking) ([s.n.], 2001)
Deel 1: 1960-1971. Deel 2: 1972-1975. Deel 3: 1976-1978. Deel 4: 1979-1981. Deel 5: 1982-1987. Deel 6: 1988-1995. Deel 7: 1996-1999. Deel 8: Chronologisch register. Deel 9: Alf. register.